TYMP Variants Result in Late-Onset Mitochondrial Myopathy With Altered Muscle Mitochondrial DNA Homeostasis - Ronchi, Dario; Caporali, Leonardo; Manenti, Giulia Francesca; Meneri, Megi; Mohamed, Susan; Bordoni, Andreina; Tagliavini, Francesca; Contin, Manuela; Piga, Daniela; Sciacco, Monica; Saetti, Cristina; Carelli, Valerio; et al. (Frontiers in Genetics, 2020)
Biallelic TYMP variants result in the Mitochondrial NeuroGastroIntestinal Encephalomyopathy (MNGIE), a juvenile-onset disorder with progressive course and fatal outcome. Milder late-onset (>40 years) form has been rarely described. Gene panel sequencing in a cohort of 60 patients featuring muscle accumulation of mitochondrial DNA (mtDNA) deletions detected TYMP defects in 3 subjects (5%), two of them with symptoms onset in the fifth decade. One of the patient only displayed ptosis and ophthalmoparesis. Biochemical and molecular studies supported the diagnosis. Screening of TYMP is recommended in adult patients with muscle mtDNA instability, even in absence of cardinal MNGIE features.